2021
DOI: 10.26858/ijole.v5i2.15787
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Perceptions on WhatsApp Integration as a Learning Tool to Develop EFL Spoken Vocabulary

Abstract: Technology integration has a great impact on learners’ learning styles and everyday life, where various encouraging responses come across in language learning institutions through the use of mobile technology. WhatsApp application instantly transfers information in different modes. At the present time it can be effectively used as a platform to engage learners with conventional classroom setting. The present study is an attempt to investigate learners’ attitudes towards WhatsApp application and their intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
(20 reference statements)
5
35
0
8
Order By: Relevance
“…Currently, online education at Saudi universities is only used to supplement the traditional face-to-face education process (Khan et al, 2021). In this study, the University discovered that it was challenging to integrate curriculum and assessment into a pure online teaching strategy, which appears to impact education worldwide (Abdelhafiz et al, 2020;Anas, 2020;Chick et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, online education at Saudi universities is only used to supplement the traditional face-to-face education process (Khan et al, 2021). In this study, the University discovered that it was challenging to integrate curriculum and assessment into a pure online teaching strategy, which appears to impact education worldwide (Abdelhafiz et al, 2020;Anas, 2020;Chick et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Literature has demonstrated that the online systems of universities are technically capable of undergoing such a transition. This is because E-learning and M-learning are being practiced even before the outbreak of COVID-19, particularly in language instruction (Khan et al, 2020(Khan et al, , 2021. Students, on the other hand, were not entirely prepared for this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shifted toward information strategies and technology is advancing at a breakneck pace [3,6,26,27,45]. Furthermore, non-textual information has become more prevalent than textual data, so it will soon become a common method of sharing data.…”
Section: B Retrieval Of Multimedia Informationmentioning
confidence: 99%
“…Education has changed rapidly in recent years, with a noticeable increase in e-learning, which involves teaching distantly or remotely and via online platforms [1][2][3]. Following the closure of all educational facilities in Saudi Arabia due to the COVID-19 breakout, an unforeseen quick transition from the typical "traditional" learning method [4,5] to the newly e-learning supported, namely, online learning, has happened. Adedoyin and Soykan [6] argue that "without the pandemic's emergence, our education institutions would not have been so adept at online instruction."…”
Section: Introductionmentioning
confidence: 99%
“…The growth of communicative pedagogy has resulted in a greater emphasis on the fundamental goal of speaking proficiency in online learning. As a result, primarily speaking competence, testing speaking skills has been a prominent issue in the language development testing process [5,14,15]. Numerous limits apply, considering the nature of verbal skills.…”
Section: Introductionmentioning
confidence: 99%